Factors influencing the incidence of the black bean aphid, Aphis fabae scop., on common beans intercropped with maize - Ogenga‐Latigo, M.W.; Baliddawa, CW; Ampofo, James Kwasi O. (1993)
The incidence of the black bean aphid, Aphis fabae check for this species in other resources scop. (Homoptera: Aphididae), and its colonization of common beans (phaseolus vulgaris L.) grown as sole crop and as intercrops with maize ( Zea mays check for this species in other resources L.) of varying growth stages was evaluated in the field and glasshouse. Modification of bean micro-climate and its effects on A. fabae, and the species range and abundance of coccinellid predators (Coleoptera: Coccinellidae) of the aphid were also assessed. Results showed that A. fabae infestation of beans was greatly reduced when intercropped with older and taller maize plants. Larger maize plants interfered with aphid colonization of beans and only small proportions of beans were infested by the aphid. Shading by older maize plants significantly (P? 0.01) reduced the level of solar radiation reaching intercropped beans; this reduced the build-up of A. fabae populations. Intercropping also reduced the number and diversity of coccinellid predators on beans, contrary to the prediction based on the "enemies hypothesis". Reduced aphid incidence on intercrop beans was attributed to maize interference with aphid host finding behavior and bean colonization and, to a lesser extent, to reduced build-up of A. fabae populations due to shading.